Influences Which Affect Reproductive Characters of Sows in Studied Reproductive Breeding - Libor Sládek; Vladimír Mikule; Kateřina Wasserbauerová (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2016)
The aim of the study was to evaluate influences which affect reproductive characters of sows in chosen reproductive breeding. These reproductive traits of sows were studied: number of all, live born and weaned piglets, losses from live born piglets till weaning. These influences which affect reproductive characters were studied: order of litter, number of piglets in litter, birth weight of piglets and influence of sex on birth weight of piglets. An average number of all born piglets per litter it was 11.74 animals. From that 11.33 live born piglets per sow and litter. 10.15 piglets were weaned from each litter in average. It represents 11.68 % of losses in live born piglets till weaning. An influence of litter order on number of live born piglets in litter was studied in an experiment. The first litters show 11.36 of live born piglets in average, the second litters 10.38 piglets, the third litters 10.43 piglets and the fourth litters 10.75 piglets. Maximum was reached on fifth litter with 13.33 of live born piglets. From the sixth litter number of live born piglets was decreasing. On the sixth litter it was 12.33 piglets, on the seventh only 9.40 of live born piglets. Between fifth litter (13.33 piglets) and seventh litter (9.40 piglets) statistical conclusive difference (P ≤ 0.05) was found. The sixth litters showed the highest number of weaned piglets – 11.00. On the contrary the lowest number of weaned piglets it was on the seventh litter – 8.40 piglets. Statistical conclusive difference among the numbers of weaned piglets according to litter order it was not proved. Higher average birth weight (1.50 kg) was found in boars in comparison to gilts (1.46 kg). Next birth weight of gilts and boars was studied in dep endence on litter order. The lowest birth weight in both sexes was found on the first litters – gilts (1.27 kg) and boars (1.36 kg). Gilts reached the highest birth weights on the seconds and the sixths litters (1.62 kg). Statistical conclusive difference (P ≤ 0.05) was found in gilts among litters one (1.27 kg) and two (1.62 kg) respectively six (1.62 kg). Boars reached the lowest birth weight (1.36 kg) on the first litter. The highest birth weight of boars (1.73 kg) was reached on the fourth litter. Statistical conclusive difference (P ≤ 0.05) was found among these litters. Next statistical conclusive difference (P ≤ 0.05) was found between the first (1.36) and sixth (1.70 kg) litter and statistical conclusive difference (P ≤ 0.01) between the first and the second litter (1.68 kg).